2022
DOI: 10.1021/acsami.2c01179
|View full text |Cite
|
Sign up to set email alerts
|

Role of Zeolite Structural Properties toward Iodine Capture: A Head-to-head Evaluation of Framework Type and Chemical Composition

Abstract: This study evaluated zeolite-based sorbents for iodine gas [I2(g)] capture. Based on the framework structures and porosities, five zeolites, including two faujasite (FAU), one ZSM-5 (MFI), one mesoMFI, one ZSM-22 (TON), as well as two mesoporous materials, were evaluated for I2(g) capture at room temperature and 150 °C in an iodine-saturated environment. From these preliminary studies, the three best-performing zeolites were ion-exchanged with Ag+ and evaluated for I2(g) capture under similar conditions. Energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 61 publications
(93 reference statements)
3
34
0
Order By: Relevance
“…These environments have moderate temperatures (i.e., T > 100 °C) and can contain oxidizing species (e.g., NO x ). Matyáš et al demonstrated that thiolated Ag 0 -functionalized silica aerogels can withstand oxidation and undergo far less aging-related effects in these environments than sorbents like Ag-MOR and this is due, at least in part, to the thiol groups helping prevent oxidation of the Ag 0 to Ag + during iodine-loading experiments. , The higher silica content is also part of the justification for why zeolites like Ag-MOR (i.e., Si/Al = 5) perform better and are more durable in these oxidizing environments than lower-silica zeolites like Ag-FAU (Si/Al ∼ 1.0–1.5 for AgX and ∼ 1.5–3.0 for AgY). ,− These types of parameters are important when comparing sorbents that might perform similarly in some testing conditions but could be very different in other conditions (e.g., higher oxidizing environments with higher temperatures) . The mechanical stability and integrity of the base sorbent are also paramount as off-gas sorbents can be subjected to large pressures in high-flow systems, and it is necessary for the sorbent to remain intact (i.e., not friable) so sorbent particles do not transport downstream in the collection system.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These environments have moderate temperatures (i.e., T > 100 °C) and can contain oxidizing species (e.g., NO x ). Matyáš et al demonstrated that thiolated Ag 0 -functionalized silica aerogels can withstand oxidation and undergo far less aging-related effects in these environments than sorbents like Ag-MOR and this is due, at least in part, to the thiol groups helping prevent oxidation of the Ag 0 to Ag + during iodine-loading experiments. , The higher silica content is also part of the justification for why zeolites like Ag-MOR (i.e., Si/Al = 5) perform better and are more durable in these oxidizing environments than lower-silica zeolites like Ag-FAU (Si/Al ∼ 1.0–1.5 for AgX and ∼ 1.5–3.0 for AgY). ,− These types of parameters are important when comparing sorbents that might perform similarly in some testing conditions but could be very different in other conditions (e.g., higher oxidizing environments with higher temperatures) . The mechanical stability and integrity of the base sorbent are also paramount as off-gas sorbents can be subjected to large pressures in high-flow systems, and it is necessary for the sorbent to remain intact (i.e., not friable) so sorbent particles do not transport downstream in the collection system.…”
Section: Introductionmentioning
confidence: 99%
“…Upon a metal-iodine reaction, the volume of the initial getter form is expanded due to the added iodine mass (e.g., Ag and Cu metal wires). This is often observed as the formation of crystalline metal-iodide complexes (e.g., AgI) and can even result in the amorphization of the scaffold crystal structure (e.g., Ag-FAU) . If these metal-iodide crystals grow too large for the scaffold to hold them effectively or the scaffold becomes friable due to the volume expansion upon iodine capture, it is possible that the process of iodine loading and scaffold amorphization could facilitate downstream release of the metal-iodide particles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… Summary of various parameters for consideration when selecting sorbents for radioiodine: (A) optimal capture performance including different types of Ag-zeolites that have different Ag loadings ( Riley et al, 2022b ) (criterion-1), (B) sorbent kinetics including examples based off actual data for I 2 ( Riley et al, 2014 ) for sulfide-based chalcogels and CH 3 I for Ag 0 -aerogels ( Tang et al, 2021 ) [in parts per billion by volume (ppbv) CH 3 I concentration streams] (criterion-2), (C) performance under relevant conditions based off data for I/Cl coadsorption ( Matyáš et al, 2021b ) and other studies in this area ( Riley et al, 2021 ; Riley et al, 2022a ) (criterion-3), (D) inherent properties of sorbent substrate ( Riley et al, 2021 ) (criterion-4), and (E) iodide stability and disposition pathways ( Riley et al, 2021 ; Reiser et al, 2022 ) (criterion-5). …”
Section: Introductionmentioning
confidence: 99%